2007
DOI: 10.1007/s10620-007-9759-7
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Factor/c-kit Receptor Signaling Enhances the Proliferation and Invasion of Colorectal Cancer Cells Through the PI3K/Akt Pathway

Abstract: In this study, we examined the role of c-kit receptor (KIT) signal transduction on the proliferation and invasion of colorectal cancer cells. We found that c-kit was expressed in 2 colorectal cancer cell lines as determined by RT-PCR, Western blot, and flow cytometry. In KIT-positive lines, KIT was activated by stem cell factor (SCF). SCF enhanced cellular proliferation of positive lines as demonstrated by the WST-1 proliferation assay. Furthermore, SCF enhanced the invasive ability of KIT-positive cell lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 30 publications
4
80
0
Order By: Relevance
“…They also have been implicated in inflammatory diseases, tissue remodeling-including fibrosis-and in liver regeneration after liver injury (Simpson et al 2003;Krieg et al 2006;Reber et al 2006). However, further studies indicate that, in addition to its physiological functions, in combination with stem cell factor, c-kit plays an important role in carcinogenesis in various tumors (Sun et al 2006;Yasuda et al 2007). Following to Mansuroglu et al (2009), liver cells will upregulate the stem cell factor or/and CD117 during cholangiocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They also have been implicated in inflammatory diseases, tissue remodeling-including fibrosis-and in liver regeneration after liver injury (Simpson et al 2003;Krieg et al 2006;Reber et al 2006). However, further studies indicate that, in addition to its physiological functions, in combination with stem cell factor, c-kit plays an important role in carcinogenesis in various tumors (Sun et al 2006;Yasuda et al 2007). Following to Mansuroglu et al (2009), liver cells will upregulate the stem cell factor or/and CD117 during cholangiocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The developing human pancreas and multiple human pancreatic cancer cell lines express both c-Kit and SCF (Table 1) [11,49,53,56]. c-Kit + cells were detected at the earliest stage of human pancreatic development, as single endocrine cells differentiated from ducts [49].…”
Section: C-kit In the Developing Human Pancreasmentioning
confidence: 99%
“…20 GSK3b activity is regulated through the canonical Wnt signaling pathway, 21 also it is modulated by the phosphatidylinositol 3 kinase/Akt (PI3K/Akt). 22 It has been shown that PI3K activity is regulated by stem cell factor (SCF)/c-Kit and platelet-derived growth factor receptor (PDGFR), 23,24 which are regulated by Notch4/Int3, 13 linking Notch4/Int3 to GSK3b. In eukaryotic cells, protein degradation occurs in the lysosomes, but the main mechanism of protein degradation is the ubiquitin-proteasome system.…”
Section: 2mentioning
confidence: 99%